Development of stratified approach to software defined networks simulation - Shkarupylo, Vadym; Skrupsky, Stepan; Oliinyk, Andrii; Kolpakova, Tetiana (Eastern-European Journal of Enterprise Technologies, 2017)
The stratified approach to software defined networks simulation has been proposed. It is based on Discrete Event System Specification formalism, atomic and coupled models concepts usage. The approach is aimed at simulation within the Windows environment, with an accent on the easiness of model reconfiguration. The proposed approach is also devoted to simulation-related overheads decrease. The atomic models of active (controller, switch, host) and passive (link) network components have been proposed. The coupled model of a software defined network comprising atomic models of active and passive components has been proposed. The estimations of the resulting coupled model complexity, with respect to the number of components basic atomic models, have been given. During experimentation, the pingall command usage scenario has been considered. For this purpose, the emulation via Mininet environment and the simulation on a basis of the proposed approach have been conducted. It has been shown that discrete-event simulation on a basis of the proposed approach is significantly less time-consuming. During the approach usage within the Windows environment, the absence of the need to utilize the Xming X Server and PuTTY utility for the purpose of visualization has been faced. The validity of the approach has been proven on a basis of the obtained experimental data. The adequacy of the resulting coupled simulation model of the network has been proven with t-criterion. The proposed approach can be used for the purpose of software defined networks validation with an accent on non-functional properties